Captain Underpants and the invasion of the incredibly naughty cafeteria ladies from outer space (and the subsequent assault of the equally evil lunchroom zombie nerds) : the third epic novel - Pilkey, Dav, 1966- (New York : Blue Sky Press, 1999)
Only Captain Underpants can stop the three evil space aliens who have invaded Jerome Horwitz Elementary School and turned everyone into lunchroom zombie nerds.
School Library Journal.
Booklist starred.
Publisher's Weekly.
4.9
3-6
730L
Keywords: Schools -- Fiction; School principals -- Fiction; Heroes -- Fiction; Cartoons and comics -- Fiction; Humorous stories; School stories; School superintendents and principals -- Fiction; Heroes and heroines -- Fiction; Humorous fiction; Schools -- Fiction; School principals -- Fiction; Heroes -- Fiction; Cartoons and comics -- Fiction; Humorous stories